2016
DOI: 10.1017/s0272263115000467
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Recasts and Gestures on the Acquisition of Locative Prepositions

Abstract: This study investigates whether gestures can be used during recasts to enhance the saliency of a target structure (locative prepositions) and to lead to better production of the target structure. Forty-eight low-intermediate English as a second language (ESL) students partook in communicative activities during which they received either no feedback (control), verbal recasts only (R), or recasts plus gesture (RG), and a subset of participants completed a stimulated recall session. Then the pretest, immediate, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 97 publications
(145 reference statements)
0
35
3
Order By: Relevance
“…Finally, the role of gestures during interaction has begun to receive attention. For example, Nakatsukasa (2016) found that the combination of gestures and recasts on English locative prepositions lead to sustained improvement on a delayed posttest compared to recasts without gestures.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the role of gestures during interaction has begun to receive attention. For example, Nakatsukasa (2016) found that the combination of gestures and recasts on English locative prepositions lead to sustained improvement on a delayed posttest compared to recasts without gestures.…”
Section: Resultsmentioning
confidence: 99%
“…However, the effects of instructional gestures on L2 pronunciation have rarely been empirically tested, and the few such reports that do exist did not find positive effects—especially when the instruction targeted individual L2 phonemic features (e.g., Hirata & Kelly, 2010; Hirata, Kelly, Huang, & Manansala, 2014). This lack of empirical support seems surprising considering the positive effects of gesture generally found in other domains (for vocabulary, see Huang, Kim, & Christianson, 2019; Kelly, McDevitt, & Esch, 2009; Macedonia & Klimesch, 2014; Tellier, 2008; for grammar, see Nakatsukasa, 2016, but cf. Nakatsukasa, 2019; for comprehension, see Sueyoshi & Hardison, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it could also specifically improve the learning of spatial categorizations that differ between the L1 and the L2. For instance, research on the efficacy of gestures during the acquisition of locative prepositions [ 74 ] showed that gestures in combination with recasts enhanced the learning of locative prepositions in a delayed post-test, in contrast to the recast-only condition. The use of gestures here can be seen as one form of embodied learning, which in addition to actions are widely used to support learning in foreign language learning and especially the acquisition of foreign language words (for a review see [ 75 ].…”
Section: Discussionmentioning
confidence: 99%